The place of silence in second language acquisition - Dat Bao (English Language Teaching and Research Journal (ELTAR-J), 2019)
The article examines the role of silence in learners’ language development by discussing current theories in second language acquisition and by connecting them to the silence phenomenon. A number of important constructs in SLA are brought up as they have potential to be associated with the silent mode of learning, namely the silent period, input, output, communicative competence, among others. The discussion also highlights a few theoretical gaps in SLA discourse that are related to silence.